Mature Surfactant Protein-B Expression by Immunohistochemistry as a Marker for Surfactant System Development in the Fetal Sheep Lung. (November 2015) - Lock, Mitchell C.; McGillick, Erin V.; Orgeig, Sandra; Zhang, Song; McMillen, I. Caroline; Morrison, Janna L.
Evaluation of the number of type II alveolar epithelial cells (AECs) is an important measure of the lung's ability to produce surfactant. Immunohistochemical staining of these cells in lung tissue commonly uses antibodies directed against mature surfactant protein (SP)-C, which is regarded as a reliable SP marker of type II AECs in rodents. There has been no study demonstrating reliable markers for surfactant system maturation by immunohistochemistry in the fetal sheep lung despite being widely used as a model to study lung development. Here we examine staining of a panel of surfactant pro-proteins (pro–SP-B and pro–SP-C) and mature proteins (SP-B and SP-C) in the fetal sheep lung during late gestation in the saccular/alveolar phase of development (120, 130, and 140 days), with term being 150 ± 3 days, to identify the most reliable marker of surfactant producing cells in this species. Results from this study indicate that during late gestation, use of anti-SP-B antibodies in the sheep lung yields significantly higher cell counts in the alveolar epithelium than SP-C antibodies. Furthermore, this study highlights that mature SP-B antibodies are more reliable markers than SP-C antibodies to evaluate surfactant maturation in the fetal sheep lung by immunohistochemistry.